Introduction to the special issue on Introducing bibliometrics in applied linguistics - Plonsky , Luke (Studies in Second Language Learning and Teaching, 2023)
It is healthy and normal for an academic discipline to reflect on its publication conventions and practices, its incentive structures, and so forth. As social scientists, it is also natural for us to want to do so in a manner that is systematic and that employs well-established empirical methods, that is, by engaging in bibliometrics (see brief history of bibliometrics in Lei et al., this issue).